Modern Warfare : lessons from Ukraine - Freedman, Lawrence; Lowy Institute for International Policy (Australia: UK: Penguin Books, Lowy Institue, 2023)
More than any other modern war, the fight between Russia and Ukraine has been a tough testing ground for modern weapons and operational concepts. Drawing on extensive research into the conduct of the war during its first year, Sir Lawrence Freedman assesses the contrasting strategies of the two sides. Ukraine has fought along classical lines, seeking victory through battle. Russia has adopted a more total approach, combining conventional battles with attacks on Ukraine's socio-economic structure. Freedman explains why the apparently superior Russian force has been unable to defeat and subjugate Ukraine.
Keywords: War; Military -- Ukraine